What Is It Like to Be a Game?—Object Oriented Inquiry for Games Research, Design, and Evaluation - Spiel, Katta; Nacke, Lennart E. (Frontiers in Computer Science, 2020)
Human-Computer Interaction (HCI) researchers more and more challenge the notion of technologies as objects and humans as subjects. This conceptualization has led to various approaches inquiring into object perspectives within HCI. Even though the development and analysis of games and players is filled with notions of intersubjectivity, games research has yet to embrace an object oriented perspective. Through an analysis of existing methods, we show how Object-Oriented Inquiry offers a useful, playful, and speculative lens to pro-actively engage with and reflect on how we might know what it is like to be a game. We illustrate how to actively attend to a game's perspective as a valid position. This has the potential to not only sharpen our understanding of implicit affordances but, in turn, about our assumptions regarding play and games more generally. In a series of case studies, we apply several object-oriented methods across three methodological explorations on becoming, being, and acting as a game, and illustrate their usefulness for generating meaningful insights for game design and evaluation. Our work contributes to emerging object-oriented practices that acknowledge the agency of technologies within HCI at large and its games-oriented strand in particular.